A Pilot Study on the Effects of Physician Gaze on Patient Satisfaction in the Setting of Electronic Health Records - Ou, Michael T.; Kleiman, Hannah; Kalarn, Sachin; Moradi, Ahmadreza; Shukla, Shweta; Danielson, Madalyn; Kaleem, Mona; Boland, Michael; Robin, Alan L.; Saeedi, Osamah J. (Journal of Academic Ophthalmology, 2019)
This study aims to determine the amount of time ophthalmologists using electronic health records (EHRs) spend looking at the patient and its correlation on patient satisfaction. This prospective cohort study examined 67 patients seeking care at two different ophthalmology clinics. Videos of entire office visits were recorded and each video was graded for amount of time spent by physicians gazing at the patient, computer, paper medical records, or other areas. Videos were also graded for the amount of time examining the patient, and the physician speaking during each visit. A patient satisfaction survey was administered at the end of each office encounter. Time of physician gaze to the patient was correlated to satisfaction outcome measures. Ophthalmologists spent 28.0 ± 21.2% of the visit looking at the computer. Overall, patient satisfaction levels were very high (4.8 ± 0.5, five-point Likert's scale). Ophthalmologists spent the same amount of time looking at patients who were extremely satisfied (28.8 ± 16.7%), as those who were not extremely satisfied (28.8 ± 15.9%). Ophthalmologists on EHRs spend over one-third of the time of each patient visit looking at the computer. However, patient satisfaction levels are very high. The amount of time that the ophthalmologist gazes at the patient or the computer does not appear to have an effect on patient satisfaction in this particular study. Further research still needs to be performed regarding the effects of EHRs on the patient experience. Physicians should continue to be sensitive to their patients' needs and approach the use of EHRs in patient encounters on an individual basis.
Keywords: electronic health record; physician gaze; electronic medical record; ophthalmology; patient satisfaction